2002
DOI: 10.1016/s1097-2765(01)00438-5
|View full text |Cite
|
Sign up to set email alerts
|

LTRPC2 Ca2+-Permeable Channel Activated by Changes in Redox Status Confers Susceptibility to Cell Death

Abstract: Redox status changes exert critical impacts on necrotic/apoptotic and normal cellular processes. We report here a widely expressed Ca2+-permeable cation channel, LTRPC2, activated by micromolar levels of H2O2 and agents that produce reactive oxygen/nitrogen species. This sensitivity of LTRPC2 to redox state modifiers was attributable to an agonistic binding of nicotinamide adenine dinucleotide (beta-NAD+) to the MutT motif. Arachidonic acid and Ca2+ were important positive regulators for LTRPC2. Heterologous L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

33
865
6
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 758 publications
(914 citation statements)
references
References 37 publications
33
865
6
3
Order By: Relevance
“…The underlying membrane currents were attributed to TRPM7, since gene silencing by siRNA targeted against TRPM7 inhibits the currents and protects neurons from cell death. One complicating factor in these studies was that molecular silencing of TRPM7 was accompanied by a parallel reduction in TRPM2, which represents another candidate channel for mediating neuronal cell death, as it is activated by reactive oxygen species (Hara et al 2002). It is therefore possible that both channels may have contributed to some of the effects on cell death.…”
Section: Physiological Functionsmentioning
confidence: 99%
“…The underlying membrane currents were attributed to TRPM7, since gene silencing by siRNA targeted against TRPM7 inhibits the currents and protects neurons from cell death. One complicating factor in these studies was that molecular silencing of TRPM7 was accompanied by a parallel reduction in TRPM2, which represents another candidate channel for mediating neuronal cell death, as it is activated by reactive oxygen species (Hara et al 2002). It is therefore possible that both channels may have contributed to some of the effects on cell death.…”
Section: Physiological Functionsmentioning
confidence: 99%
“…20,21 Transient receptor potential M2 channel (TRPM2) (previously LTRPC2 or TRPC7) is a Na þ -and Ca 2 þ -permeable nonselective cation channel and can be activated by exposing TRPM2-expressing cell lines to H 2 O 2 . [22][23][24] ADP ribose (ADPR) is suggested as a downstream messenger for TRPM2 opening, since one domain of TRPM2, which is homologous to NUDT9 ADR hydrolase, binds ADPR. 25 However, it has also been suggested that NAD þ directly gates the channel, 22,26 since 32 P-labeled b-NAD þ binds strongly to the C-terminus of TRPM2.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, TRPM2, TRPM3 and TRPM8 are Ca 2+ permeable nonselective cation channels, which differ substantially with respect to their activation stimuli (Chuang et al 2004;Grimm et al 2003;Hara et al 2002;Lee et al 2003;McKemy et al 2002;Peier et al 2002;Sano et al 2001;Wehage et al 2002). TRPM8 is activated by low temperature (Chuang et al 2004;Voets et al 2004a), while TRPM2 is stimulated by intracellular ADP-ribose, NAD + and oxidative stress (Hara et al 2002;Perraud et al 2001Perraud et al , 2003). TRPM3 appears to be activated by hypoosmotic cell swelling, rises of intracellular Ca 2+ and by D-erythro-sphingosine (Grimm et al 2003(Grimm et al , 2004Lee et al 2003).…”
Section: Introductionmentioning
confidence: 99%